Industrial organization : contemporary theory and practice - Pepall, Lynne. (South-Western College, 1999)
Introduction. Production technology and market structure. Basic monopoly pricing and product strategies. Product and pricing strategies for the multiproduct monopolist. Theories of business strategy in oligopoly markets. Monopoly power and predatory conduct. Collusion and cartels. Mergers. Vertical relationa and restraints. Advertising. Research and development. Strategic commitments.